2015
DOI: 10.1007/s00264-015-2810-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Charlson comorbidity index in patients undergoing revision total hip arthroplasty

Abstract: In summary, we conclude that the CCI and the age-related CCI are strong predictors regarding complication rate in patients undergoing RTHA. In a short- to mid-term follow-up, no influence on implant survival is detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 28 publications
1
33
2
1
Order By: Relevance
“…Myocardial infarction, congestive heart failure, mild liver disease and renal disease increase the risk of IHPC. These findings are consistent with those of previous studies [ 17 , 35 37 ]. Koenig et al [ 36 ] found that both age and CCI were independent predictors of major adverse events after RHA (adjusted OR, 1.04; 95%CI, 1.00–1.07; and adjusted OR, 1.22; 95%CI, 1.03–1.45, respectively).…”
Section: Discussionsupporting
confidence: 94%
“…Myocardial infarction, congestive heart failure, mild liver disease and renal disease increase the risk of IHPC. These findings are consistent with those of previous studies [ 17 , 35 37 ]. Koenig et al [ 36 ] found that both age and CCI were independent predictors of major adverse events after RHA (adjusted OR, 1.04; 95%CI, 1.00–1.07; and adjusted OR, 1.22; 95%CI, 1.03–1.45, respectively).…”
Section: Discussionsupporting
confidence: 94%
“…The number of patients with each Charlson Comorbidity Index (CCI) was also obtained with the mean, median, and SD. This information can be used to estimate 10-year mortality [8], and CCI has been validated in revision THA [37].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that these risks of surgery, including both morbidity and mortality, increase with age as well as preoperative comorbidity status. 23,28,32 Both age and comorbidities of the patients in our data set were analyzed to further elucidate the mechanics behind the shift from fasciectomies and fasciotomies to CCH injection. The percentage of patients receiving fasciectomies decreased significantly across all age groups, though by greater amounts in the older populations.…”
Section: Discussionmentioning
confidence: 99%